2022
DOI: 10.1111/jdv.18688
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and network meta‐analysis of different types of emollient for the prevention of atopic dermatitis in infants

Abstract: Prophylactic application of emollients has been an effective strategy against infant atopic dermatitis (AD); however, the difference of different emollients is unknown. We performed this network meta‐analysis to compare different emollients in preventing infant AD. A systematic search was performed in PubMed, EMBASE and Cochrane library to identify relevant studies from their inception through 28 February, 2022. We evaluated the quality of eligible studies using the Cochrane risk of bias assessment tool. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This conclusion did not apply to neonates with risk factors of AD development, among whom such an intervention decreases disease incidence. The meta-analyses emphasized the complications and negative aspects of emollient use, such as the increased risk of skin infectious diseases among neonates treated with emollients [42][43][44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion did not apply to neonates with risk factors of AD development, among whom such an intervention decreases disease incidence. The meta-analyses emphasized the complications and negative aspects of emollient use, such as the increased risk of skin infectious diseases among neonates treated with emollients [42][43][44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…The emollient types used in the intervention groups differed and included formulas such as creams, oils, gels, balms, and emulsions. The systemic review and metaanalysis by Junqin Liang et al [45] showed that emollient emulsion might be the superior option for preventing AD development in infants. Emollients may contain lipids that are nonphysiological, including petrolatum or lanolin, or physiological, which mimic lipids naturally present in the stratum corneum such as ceramides and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Different pair-wise meta-analyses took into account all these studies and finally did not find that emollient application prevents either sensitization to food allergen or FA. 50,56,57 The heterogeneity of the studies that have been included in these meta-analyses (I 2 = 41%, 57 40%, 56 and 66% 50 ) forces to consider them with precaution.…”
Section: Whatdoclini C Altrial Ssayon Emollienteffec Tivene Sstopre V...mentioning
confidence: 99%
“…Overall atopic dermatitis occurred less frequently when emollients were used for prevention (RR 0.64, CI 0.47-0.88; p < 0.001). 11 Some patients with atopic dermatitis when treated with Dupilumab develop facial erythema. This phenomenon was studied in 162 patients with severe atopic dermatitis under Dupilumab treatment; 137 had facial erythema before Dupi treatment, 121 improved, seven got worse and six out of 25 patients developed new facial erythema under Dupilumab.…”
Section: A L L Ergy/ecz E M Amentioning
confidence: 99%
“…In a systematic review and network meta‐analysis, the effect of primary prevention with emollients was studied in 11 double‐blind controlled randomized studies in a total of 3483 patients. Overall atopic dermatitis occurred less frequently when emollients were used for prevention (RR 0.64, CI 0.47–0.88; p < 0.001) 11 …”
Section: Allergy/eczemamentioning
confidence: 99%